2019
DOI: 10.24911/ejmcr/173-1540307083
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral osteomyelitis due to an unusual pathogen: a case report

Abstract: Background: Vertebral osteomyelitis most often presents with back pain and is usually a secondary complication of a distant infection with hematogenous seeding. A source of infection is detected in about half of the cases. Burkholderia cepacia has rarely been implicated as an etiology. Case Presentation: We present a 50-year old Caucasian male with low back pain for 10 days associated with urinary incontinence without any fever or chills. He had laboratory and imaging evidence of vertebral osteomyelitis. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…This case is also remarkable because B. cepacia rarely causes osteomyelitis and discitis. Most cases are related to spinal surgery, trauma, intravenous drug use, or postoperative complications [ 4 , 12 16 ]. One case-control study of non-CF patients found recent abdominal surgery to be an independent risk factor for Burkholderia cepacia bacteremia [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…This case is also remarkable because B. cepacia rarely causes osteomyelitis and discitis. Most cases are related to spinal surgery, trauma, intravenous drug use, or postoperative complications [ 4 , 12 16 ]. One case-control study of non-CF patients found recent abdominal surgery to be an independent risk factor for Burkholderia cepacia bacteremia [ 17 ].…”
Section: Discussionmentioning
confidence: 99%